2017
DOI: 10.1177/0306624x17741593
|View full text |Cite
|
Sign up to set email alerts
|

Parolee–Parole Officer Rapport: Does It Impact Recidivism?

Abstract: Parole officers are an integral part of parolees' reentry process and success. Few studies, however, have examined whether the quality of the relationship between parolees and their parole officer influences outcomes such as recidivism. This study assesses how recidivism is affected by the quality of the relationship that parolees have with their parole officers. Using the Serious and Violent Offender Reentry Initiative (SVORI) dataset, we use parolees' perceptions of their relationship with their parole offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 56 publications
(71 reference statements)
3
35
0
Order By: Relevance
“…Drawing from the perspective of DCSS theory, other individuals and/or social groups could fill this role and deliver instrumental support. Supporting this proposition, recent studies (e.g., Chamberlain et al 2018; Vidal, Oudekerk, and Reppucci 2015) show that individuals can derive social support from their probation/parole officer. As such, people who do not have family contact could potentially still benefit from the instrumental support that stems from other important social groups such as supervision officers, supportive peers, or members of a faith community during reintegration.…”
Section: Resultsmentioning
confidence: 89%
“…Drawing from the perspective of DCSS theory, other individuals and/or social groups could fill this role and deliver instrumental support. Supporting this proposition, recent studies (e.g., Chamberlain et al 2018; Vidal, Oudekerk, and Reppucci 2015) show that individuals can derive social support from their probation/parole officer. As such, people who do not have family contact could potentially still benefit from the instrumental support that stems from other important social groups such as supervision officers, supportive peers, or members of a faith community during reintegration.…”
Section: Resultsmentioning
confidence: 89%
“…This finding both confirms previous research regarding the importance of communication strategies and demonstrates the feasibility of using a categorical approach to examining supervision contacts and practices. Adding Chamberlain and colleagues’ (2017) results that the type of rapport officers and those they supervise have affected recidivism, these findings suggest that there are specific training and performance support approaches that parole officers and their supervisors can use to affect positive change on parole outcomes. However, the widespread application of a balanced approach and evidence-based communication skills will require more work (Viglione, Rudes, & Taxman, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…The first is the establishment of a relationship with the person under supervision that is characterized as high in trust, respect, and collaboration (Skeem et al, 2007), and where personal autonomy is valued (Bonta & Andrews, 2010) and authority is used effectively (Dowden & Andrews, 2004). Quality supervisory relationships are thought to facilitate successful outcomes by motivating the persons being supervised to adhere to supervision conditions and treatment recommendations (e.g., Chamberlain et al, 2018), as well as by encouraging them to seek assistance during periods of crisis or stress (e.g., Ireland & Berg, 2008). For example, Kennealy et al (2012) revealed that the quality of the relationship between officers and people under supervision is associated with increased success on parole and longer time to rearrest.…”
Section: A Theoretical Model Of Changementioning
confidence: 99%